2022
DOI: 10.1029/2022ef002897
|View full text |Cite
|
Sign up to set email alerts
|

Global‐Scale Shifts in Rooting Depths Due To Anthropocene Land Cover Changes Pose Unexamined Consequences for Critical Zone Functioning

Abstract: Rooting depth is an ecosystem trait that determines the extent of soil development and carbon (C) and water cycling. Recent hypotheses propose that human‐induced changes to Earth's biogeochemical cycles propagate deeply into Earth's subsurface due to rooting depth changes from agricultural and climate‐induced land cover changes. Yet, the lack of a global‐scale quantification of rooting depth responses to human activity limits knowledge of hydrosphere‐atmosphere‐lithosphere feedbacks in the Anthropocene. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 92 publications
(203 reference statements)
0
7
0
Order By: Relevance
“…Simultaneously with erosion, the imposition of modern crops across landscapes is responsible for the removal of what otherwise would be perennial vegetation. Averaged globally, roots have shallowed since the imposition of agriculture on our planet; indeed, of the ∼48% of Earth's land surface that has experienced root shallowing, 2.3 × 10 7 km 2 have experienced root shallowing due to agricultural expansion (Hauser et al., 2022). Because roots and the microbes that thrive in the rhizosphere serve as biotic weathering agents, root shallowing could conceivably reduce deep soil‐weathering rates.…”
Section: Current Approaches To Constrain the Base And Thickness Of Th...mentioning
confidence: 99%
“…Simultaneously with erosion, the imposition of modern crops across landscapes is responsible for the removal of what otherwise would be perennial vegetation. Averaged globally, roots have shallowed since the imposition of agriculture on our planet; indeed, of the ∼48% of Earth's land surface that has experienced root shallowing, 2.3 × 10 7 km 2 have experienced root shallowing due to agricultural expansion (Hauser et al., 2022). Because roots and the microbes that thrive in the rhizosphere serve as biotic weathering agents, root shallowing could conceivably reduce deep soil‐weathering rates.…”
Section: Current Approaches To Constrain the Base And Thickness Of Th...mentioning
confidence: 99%
“…Provided that Earth´s soils have lost ca. 14.000 km 3 of rooted volume due to the agricultural conversion of native habitats (Hauser et al, 2022), it is a priority to breed crop root traits that recover part of this carbon sink. (4) Other dimensions of crop phenotypes that should be targets of sustainability‐oriented breeding include improved floral reward for pollinators in pollinator‐dependent crops (Garibaldi et al, 2013), local adaptation of traits through backcrossing elite varieties with landraces (Meseka et al, 2015) and breeding for nutritional quality instead of plain calorie supply (Graham et al, 2007).…”
Section: How To Use Knowledge On Crops´ Reactions To Domestication To...mentioning
confidence: 99%
“…Accessible to ecosystems implies that groundwater might also be a convenient human water source. Globally, 96.9% of plants root no deeper than 10 m 35 and are projected to get shallower in agricultural areas 16 . We lack global data on groundwater connectivity to aquatic ecosystems, but two-thirds of US streams that potentially gain water from their surrounding aquifers lie in regions with water table depths no deeper than 10 m 7 .…”
Section: Groundwater Accessibility For Ecosystems and Humans Varies G...mentioning
confidence: 99%
“…As vegetation may rely on groundwater directly or through capillary rise 4 , knowledge about the depth of the groundwater table is a central building block in developing global carbon policy 14 . Recent studies showed that tropical forests may even change from carbon sinks to carbon sources due to water stress 15 and that global land cover changes affect rooting depth and thus carbon and water cycling 16 .…”
mentioning
confidence: 99%